Educational Transformation: Leveraging Knowledge Management for Student Success - Jailani, Mohammad; Jamroji, Sulhan; Perawironegoro, Djamaluddin; Huda, Miftachul (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
The high cost (cost) of honorary coaches from outside, causing the school budget to swell. Therefore, schools need the implementation of knowledge management, to improve teacher competence to improve student achievement outcomes. The purpose of this study was to analyze knowledge management in improving student achievement outcomes. This research was conducted at SD Muhammadiyah Nitikan Yogyakarta, the reason for choosing SD Muhamadiyah Nitikan Yogyakarta as the object of research to analyze the implementation of knowledge management. This type of research is a qualitative approach, the subject of this research is the teacher. Subjects were determined by purposive sampling technique, to obtain accurate information. Data collection techniques were carried out by interview, observation, and documentation methods. The data analysis technique followed the Mules and Huberman model with data display, data reduction, and data verification. Data validity by triangulation. The results of this study found that knowledge management can help reduce the cost of achievement. This affects the increasing competence of teachers to maximize the results of achievement. Schools no longer take mentors from outside, because it is enough to minimize the coaches from SD Muhamamdiyah Nitikan Yogyakarta. Both in increasing academic and non-academic achievement results. The implication of this research is to improve the quality of schools and increase the confidence of students and parents in sending their children to school.